2019
DOI: 10.1002/erv.2687
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic alliance in inpatients with severe anorexia nervosa

Abstract: Objective Therapeutic alliance (TA) is a relevant aspect in anorexia nervosa (AN), but data on inpatients are lacking. We aimed to evaluate the influence of motivation to change, diagnostic subtypes, and duration of illness on TA at hospital discharge; we also investigated if baseline clinical characteristics were associated with discharge TA, and the TA‐outcome association. Method We enrolled 137 adult inpatients with AN completing Eating Disorder Examination‐Questionnaire, Beck Depression Inventory, State–Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
43
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(51 citation statements)
references
References 52 publications
6
43
0
2
Order By: Relevance
“…These findings relating illness duration concur with most of the previous literature (Andrés-Perpiñá et al, 2020;Fichter, Quadflieg, & Hedlund, 2006;Le Grange et al, 2014;Marzola, Albini, Delsedime, Fassino, & Abbate-Daga, 2019) and are also confirmed by recent systematic reviews (Austin et al, 2021;Ghaderi et al, 2018;Gregertsen, Mandy, Kanakam, Armstrong, & Serpell, 2019;Linardon, Kothe, & Fuller-Tyszkiewicz, 2019). Based on our data, successful recovery from BN is more probable if treatment is provided before the illness reaches 13-14 years of duration.…”
Section: Predictive Models Of Therapy Nonresponse and Drop-outsupporting
confidence: 92%
“…These findings relating illness duration concur with most of the previous literature (Andrés-Perpiñá et al, 2020;Fichter, Quadflieg, & Hedlund, 2006;Le Grange et al, 2014;Marzola, Albini, Delsedime, Fassino, & Abbate-Daga, 2019) and are also confirmed by recent systematic reviews (Austin et al, 2021;Ghaderi et al, 2018;Gregertsen, Mandy, Kanakam, Armstrong, & Serpell, 2019;Linardon, Kothe, & Fuller-Tyszkiewicz, 2019). Based on our data, successful recovery from BN is more probable if treatment is provided before the illness reaches 13-14 years of duration.…”
Section: Predictive Models Of Therapy Nonresponse and Drop-outsupporting
confidence: 92%
“…Furthermore, this data could illuminate how responsive those with a longer DOI can be to structured and short-term treatments, as other research has suggested [4,19]. In keeping with earlier research from our group [47] patients with LD showed a therapeutic alliance comparable to that of the younger ones. Interestingly, those with a shorter DOI improved less in the drive for thinness and body shape concerns, mirroring a network analysis showing patients with a shorter DOI reporting overvaluation of weight or shape as key elements [48].…”
Section: European Psychiatrysupporting
confidence: 87%
“…A strong therapeutic alliance in patients with anorexia nervosa has been found to predict treatment completion and change in eating-related psychopathology, both at discharge and at 1-year follow-up. 13,14,15 Evaluating Options Ideally, the team should consider urgent transfer to a specialty behavioral program for the care of patients with eating disorders, especially if VV has not been treated in one before or has left treatment prematurely on past admissions. Expert eating disorders behavioral specialty programs can improve eating disorder symptomatology and weightrestore a majority of patients using a multidisciplinary approach that includes individual, group, and family-based treatments; supervised meals; and behavioral contingency management strategies.…”
Section: Commentarymentioning
confidence: 99%